Effect of temperature and light intensity on early infection behaviour of a Western Australia isolate of Plasmopara viticola, the downy mildew pathogen of grapevine - Williams, Mia; Magarey, P.; Sivasithamparam, K. (CSIRO Publishing, 2007)
Grape downy mildew, caused by Plasmopara viticola, is a relatively new disease in Western Australia (WA). The effect of temperature and light intensity on zoospore germination and penetration of stomatal apertures by a WA isolate of P. viticola in the presence of free water on leaf discs of grapevine (Vitis vinifera) is described. Germination and penetration commenced within the first hour following inoculation. Zoospores germinated at temperatures ranging from 5 to 30◦C, but not at 35◦C. Germ tubes penetrated stomatal apertures at temperatures ranging from 10 and 25◦C, but not at 30 or 35◦C and rarely at 5◦C. A 20◦C dark environment favoured zoospore germination and host penetration, whereas both infection events occurred at a lower frequency in the light. Light exerted an inhibitory effect on the development of zoospores soon after their release from sporangia. This in turn influenced the infectivity of the pathogen.